Why do patients want information if not to take part in decision making?. Issue 12 (8th September 2010) - Manson, Neil C
Abstract : There is empirical evidence that many patients want information about treatment options even though they do not want to take a full part in decision-making about treatment. Such evidence may have considerable ethical implications but is methodologically problematic. It is argued here that, in fact, it is not at all surprising that patients' informational interests should be separable from (and often stronger than) their interests in decision-making. A number of different reasons for wanting information are offered, some to do with the content of information; some with the process, others with the fact or occasion of informing. This philosophical clarification leads to some suggestions for further empirical study.